Developing moral values among english language learners - Ibragimova, Jamila Y. (2021)
The paper presents the results of a theoretical and methodological study of the difficulties and opportunities of developing students' moral values among English language learners ​​in the system of modern education. The moral education of students in the context of the ongoing digitalization of society, caused by world transformation and globalization, requires a specific analysis and development of new approaches to the formation of moral norms and personal values. The authors determine methodological approaches to moral values among English language learners, considering the historical experience and achievements of the past's classical domestic psychological and pedagogical science. The analysis results allowed the authors to conclude that the solution to the problem of the development of the moral values ​​of students in the context of global digitalization is possible by relying on the new theory of moral education, the system of provisions, and methodological principles.